1995
DOI: 10.1159/000239320
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility Tests with Fastidious and Nonfastidious Bacterial Reference Strains: Effects of Aerobic versus Hypercapnic Incubation

Abstract: Representative antimicrobial drugs were examined under aerobic and hypercapnic (3 and 5% v/v CO2) incubation with the Bauer-Kirby agar disk diffusion, a broth microdilution method, and the agar dilution procedure against nonfastidious, standard ATCC quality control strains and against two Β-hemolytic streptococcal, two pneumococcal, and three Haemophilus influenzae ATCC strains. It was found that an atmosphere of 3-5% CO2 merely antagonized amikacin, gentamicin, and netilmicin; the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Likely, the increase of lipophilicity, due to the methylation of the carboxyl group, facilitate the transport of this substance through outer membrane of the Gram-negative cell, once it is formed by lipoproteins, lipopolysaccharides, and phospholipids. The values found in the microrganisms-test for the reference compounds, tetracycline, ampicillin and fl uconazol, were in accordance with those reported in the literature (Pfaller et al, 1995;Traub;Leonhard, 1995).…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…Likely, the increase of lipophilicity, due to the methylation of the carboxyl group, facilitate the transport of this substance through outer membrane of the Gram-negative cell, once it is formed by lipoproteins, lipopolysaccharides, and phospholipids. The values found in the microrganisms-test for the reference compounds, tetracycline, ampicillin and fl uconazol, were in accordance with those reported in the literature (Pfaller et al, 1995;Traub;Leonhard, 1995).…”
Section: Antimicrobial Activitysupporting
confidence: 90%
“…This phenomenon corresponds to increased lipophilicity of the molecule, wich permits penetration into cell membranes (9). The MIC values of these two compounds are equivalent to those described in the literature for a great number of commercial antibiotics used in clinical treatments (8,10,11). E. coli was not sensitive to the substances tested.…”
mentioning
confidence: 89%
“…Disk susceptibility tests were carried out according to the method of Bauer et al [4]; the diameters of the inhibition zones were interpreted using the latest NCCLS criteria [5], The agar dilution method [2] served to determine the minimal inhibitory concentra tions (MICs) of the two glycopeptide antibiotics. The bacterial suspensions in saline (turbidity = McFarland Values are the diameters (mm) of inhibition zones.1 = Intermediate disk susceptibility; R = resistance (disk); ND = not done.…”
Section: Antimicrobial Susceptibility Testsmentioning
confidence: 99%
“…Recent investigations regarding the inhibi tory activities of several antimicrobial drugs against diverse fastidious and nonfastidious bacteria on/in various media disclosed that chocolatized (80°C, 13 min) Mueller-Hinton agar (CHOC-MHA), which contained 5% (vol/vol) defibrinated sheep blood, antago nized the glycopeptide antibiotics teicoplanin and vancomycin against enterococci, pneu mococci, staphylococci, and streptococci [1,2], Very recently, Jensen ct al. [3] observed that 5% (vol/vol) horse blood in various me dia antagonized teicoplanin and vancomycin; however, chocolatized media were not inves tigated.…”
Section: Introductionmentioning
confidence: 99%